Detrital zircons from the Yakutat terrane, Alaska: Differentiating the Schist of Nunatak Fiord from the Yakutat Group flysch and mélange. - Olson, Haley Caldwell (Carleton Digital Commons, 2017)
The basement of the southeastern Alaskan Yakutat terrane is composed of Eocene basalt and the Late Cretaceous and Paleocene Yakutat Group, which contains a flysch unit and a mélange unit. Near Yakutat, Alaska, the fault-bounded Boundary block contains the Schist of Nunatak Fiord and is located between the outboard Yakutat block and the inboard Chugach Metamorphic Complex. I use detrital zircon U/Pb and Hf isotope data to differentiate the Schist of Nunatak Fiord from the Yakutat Group flysch and mélange. The Schist of Nunatak Fiord samples yield maximum depositional ages between 53.2 Ma and 68.9 Ma. The most prominent Schist of Nunatak Fiord grain-age distribution peaks occur at 62 Ma and between 72 Ma and 76 Ma, with subordinate peaks between 151 Ma and 194 Ma. The number of Precambrian grains from the Schist of Nunatak Fiord varies (n=0, n=3, n=18, and n=32). One sample (n=18) has a prominent peak at 1550 Ma. Another (n=32) has prominent peaks at 1400 Ma and 1740 Ma. Samples from the Yakutat Group flysch and mélange have maximum depositional ages that range from 60.4 Ma to 101 Ma, but the majority are Late Cretaceous to Paleocene with prominent peaks at ~74, ~91 Ma, ~1380 Ma, and ~1710 Ma. The Phanerozoic zircons from the Schist of Nunatak Fiord have εHf(t) values ranging from -2.0 to +12.1, compared to the -31.3 to +11.9 values from the Yakutat flysch and mélange. These data indicate that the Schist of Nunatak Fiord is younger, more heterogeneous, and from a more juvenile source than the Yakutat Group flysch and mélange. The Precambrian grain-age distributions and εHf(t) values point to a juvenile southern Laurentian source terrane for the Yakutat Group sediments.